Analisis Kelayakan Usaha Tani Ubi Jalar (Studi Kasus Di Kampung Bersehati Distrik Tanah Miring Merauke) - Gregorius Andana; Maria M.D Widiastuti; Untari Untari (Musamus Journal of Agribusiness, 2021)
This study aims to determine the feasibility of sweet potato farming in Bersehati Village, Tanah Miring District, Merauke Regency. The determination of the research location was carried out by purposive sampling with the consideration that the area was a sweet potato producing area with a business duration of more than 5 years. The number of respondents in this study were 15 people. Analysis of the data used is the financial analysis of the R/C ratio. The results of this study indicate that the farming profits obtained from these 3 types of sweet potatoes are different, where the sweet potato with red skin and white content with a total revenue of Rp. 50,000,000 able to get a profit of Rp. 30,250,000 with an R/C ratio of 2.5. This amount is greater than the profit of red sweet potato filled with purple content with a total revenue of Rp. 42,000,000 with a profit of Rp. 20,550,000 and R/C ratio 1.96. While the white sweet potato with purplish white content with a total revenue of Rp. 43,200,000 can get a business profit of Rp. 21,850,000 with an R/C ratio of 2.02, which is below the business profit of white filled red skin sweet potatoes and higher than purple filled red skin sweet potatoes.